A novel transdermal ketoprofen formulation for analgesia in cattle. Issue 6 (4th September 2022) - Mills, Paul C.; Owens, Jane G.; Reinbold, James B.; McGowan, Michael; Ellenbergner, Claudia; Woldeyohannes, Solomon; Satake, Nana
Abstract: Ketoprofen is registered in many countries for injectable administration in cattle. Because it is soluble in a wide range of excipients, development of a novel transdermal (TD) ketoprofen formulation was pursued to provide a convenient and pain‐free route of administration in cattle. One hundred and six excipient combinations were screened using in vitro techniques (Franz diffusion cells), with a 20%(w/v) ketoprofen formulation dissolved in a combination of 45%:45%(v/v) ethanol and isopropyl myristate (IPM) and 10%(v/v) eucalyptus oil achieving maximal penetration of ketoprofen through bovine skin. A bioavailability study was then conducted using a randomized cross‐over design ( n  = 12), including IV, IM (both 3 mg/kg) and TD (10 mg/kg) ketoprofen formulations administered with a one‐week washout period between administrations. The IV and IM formulation pharmacokinetic results were as expected. The C MAX, T max and AUC0‐Last were significantly higher (arithmetic mean ± SD) after TD administration (20.0 ± 6.5 μg/ml, 115 ± 17 min and 3940 ± 1324 μg*min/ml, respectively), compared to IM (11.0 ± 4.0 μg/ml, 74 ± 43 min and 2376 ± 738 μg*min/ml, respectively), although there were no significant differences for T½β . However, dose corrected values C MAX and AUCinf were significantly higher for IM compared to TD. The arithmetic mean bioavailability (F) of the transdermal formulation was 50%. The plasma concentration of the TD formulation at a dose of 10 mg/kg was similar to the IM formulation at 3 mg/kg by 30 min post‐dosing with an arithmetic mean ± SD of 7.97 ± 4.38 vs. 8.02 ± 3.55 μg/ml, respectively. The TD formulation was generally well tolerated by cattle, although some local irritation along the site of application was noted after 12 h of exposure during the bioavailability study. Results indicate that this novel TD formulation provides a substantial improvement in administration convenience, may improve animal welfare and end‐user safety through needle‐free administration, and achieves similar plasma pharmacokinetics to the IM product when administered at 10 mg/kg.